A Review of Infectious Diseases Associated with Religious and Nonreligious Rituals. (6th December 2021) - Gajurel, Kiran; Deresinski, Stan
Abstract : Rituals are an integral part of human life but a wide range of rituals (both religious and non-religious), from self-flagellation to blood brotherhood to ritual sprinkling of holy water, have been associated with transmission of infections. These infections include angiostrongyliasis, anthrax, brucellosis, cholera, COVID-19, cutaneous larva migrans, Ebola, hepatitis viruses, herpes simplex virus, HIV, human T-cell leukemia virus (HTLV), kuru, Mycobacterium bovis, Naegleria fowleri meningoencephalitis, orf, rift valley fever, and sporotrichosis. Education and community engagement are important cornerstones in mitigating infectious risks associated with rituals.